2018
DOI: 10.1001/jamaophthalmol.2017.5849
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery Outcomes in Eyes With Primary Epiretinal Membrane

Abstract: IMPORTANCE Primary epiretinal membrane (ERM) is a common retinal disorder with a prevalence of 4% to 18.5%. Although ERM and cataracts commonly occur together, to our knowledge, no studies have investigated the outcome of cataract surgery alone in this setting. OBJECTIVE To analyze the visual outcome and cystoid macular edema risk with cataract surgery in eyes with primary ERM. DESIGN, SETTING, AND PARTICIPANTS In this retrospective clinical database study, data were collected from July 2003 to March 2015 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…1,2,6,[21][22][23][24] We have found an improvement in visual acuity from 0.5 log-MAR to 0.2 logMAR, which corresponds to an increase of approximately three lines in the Snellen charts, which was similar to the results described by other authors in their analysis. 9,25,26 This increase on BCVA was independent of the phakic status of the patient, because both phakic and pseudophakic eyes were considered in our sample and no significant differences were noted in both pre and post-operative BCVA (Mann-Whitney U; p = 0.93). Concomitant or subsequent cataract surgery was also proved to be the same in terms of refractive error, BCVA, or CMT.…”
Section: Discussionmentioning
confidence: 86%
“…1,2,6,[21][22][23][24] We have found an improvement in visual acuity from 0.5 log-MAR to 0.2 logMAR, which corresponds to an increase of approximately three lines in the Snellen charts, which was similar to the results described by other authors in their analysis. 9,25,26 This increase on BCVA was independent of the phakic status of the patient, because both phakic and pseudophakic eyes were considered in our sample and no significant differences were noted in both pre and post-operative BCVA (Mann-Whitney U; p = 0.93). Concomitant or subsequent cataract surgery was also proved to be the same in terms of refractive error, BCVA, or CMT.…”
Section: Discussionmentioning
confidence: 86%
“…In the long term, however, it appears that baseline phakic patients visually outperform pseudophakic patients by a wide margin. Hardin et al 16 have also shown that cataract extraction alone in patients with comorbid primary ERMs can lead to an increase in BCVA of 0.27 logMAR units within 4-12 weeks postoperatively, a significant increase in visual function of roughly 3 Snellen lines.…”
Section: Discussionmentioning
confidence: 96%
“…Our data shows a statistically significant increase in all these variables. As literature has previously demostrated [7], the presence of an epiretinal membrane is an independent risk factor, which acts sinergically to increase the rate of these inflammatory consequences [13]. Detailed analysis of foveal OCT anatomy was performed demonstrating the changes induced by phacoemulsification in eyes with idiopathic advanced membranes.…”
Section: Discussionmentioning
confidence: 99%